(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article deals with the issue of education of human rights in the spirit of national values in Uzbekistan. Today, our state has shown the methods of educating people in order to increase the legal and moral consciousness in society. It is emphasized that the construction of civil society and its improvement is not only legal awareness, but also awareness of responsibility by our citizens.